(untitled) (Transport systems and technologies, 2022)
For the preparation and during the execution of the work, experimental and theoretical studies were carried out on the influence of the state of the rolling surface profile of the wheelset on the level of interaction forces between the elements of the rail track and rolling stock in operation on the railways of Ukraine. Approaches to modeling the influence of the rolling surface profile of wheelsets on the stability of the wheelset movement and force interaction with the rail track were further developed. Experimental studies of the wear of the rolling surface of wheelsets of rolling stock were carried out, the intensity of their wear depending on the mileage of the locomotive was investigated. Studies of the influence of technical characteristics of hardness in the interaction of rail and wheel and their impact on the service life on the railways of Ukraine are analyzed. After the beginning of operation of wheelsets with increased hardness value, the optimal ratio of hardness of rail and wheel steel was violated. From various sources on the interaction of rails and wheels it is known that the best wear resistance in a friction pair is shown by metals with approximately the same hardness. Based on the data obtained, their analysis was carried out with the development of recommendations for further operation.